The Swiss National Bank's fear of float - Kristin Berthold; Georg Stadtmann (Journal of Central Banking Theory and Practice, 2019)
We theoretically examine under which assumptions the impossible trinity holds. We also focus on the most recent Swiss experience and ask whether the SNB gained monetary independence by switching from a fixed to a floating exchange rate system in January 2015. The theoretical examination shows that the impossible trinity holds under the following assumptions: Equality of domestic and foreign real interest rates, the quantity theory of money holds, and that the relative PPP is fulfilled. The empirical analysis reveals that relative PPP does not hold for the Swiss case and it was necessary for the SNB to adopt its monetary policy in accordance with the ECB's expansionary monetary policy. We show that for a small open economy, such as Switzerland, whether the central bank implements a fixed or a floating exchange rate system does not play a role in its monetary policy independence.
Keywords: E52; E58; E42; 330; Foreign exchange market; Swiss crisis; impossible trinity; monetary policy independence.